A Study Protocol for a Randomized Trial on Effect of Safe Patient Handling (SPH) program on Rehabilitation Outcomes and on Safety of Physical Therapists in Rural Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Patient management and intervention practices are a crucial component of patient treatmentin the hospitals. In recent times the focus is put on early and regular mobilization of patients to boost recoveryduring and after hospitalization. Increase in inpatient mobilization to improve patient treatment raises aphysiotherapist’s physical demands and therefore risk of injury. With the context of a patient mobilizationprogram, better work procedures and decrease in physiotherapist’s injuries while working, SPH programwill be incorporated.Purpose : The goal of this research is to evaluate the effect of SPH program and mobilization in context ofefforts to improve quality of health care and safety of patients as well as the physical therapist.Method : There will be 2 groups, intervention (SPH) and comparison (no-SPH) each group will consist of20 patients. The intervention group will be consisting the patients admitted in rehabilitation unit for the firstthree months of the research and the comparison group will consist the patients admitted in rehabilitationunit in the last 3 months of the research. Intervention group will undergo rehabilitation with SPH programwhich will include equipments like lifts based on ceiling and floors, sit to stand supports, motorized hospitalbeds and ambulation aids.Result : Statistical analysis will be conducted. Comparison will be made on a variety of characters such asage, duration of stay and diagnosis to determine equivalence between the groups. Evaluation of the impactof SPH program on recovery outcome will be done by linear regression model. FIM scores of interventiongroup at admission and discharge will be compared to the comparison group FIM scores at the time ofadmission and discharge. The linear regression model will represent the graphical overview of the meanmobility scores at the time of admission and at the time of discharge for each group.Conclusion: The publication of conclusion will be done after conducting the study and obtaining the resultsthrough statistical analysis.